Low-Intensity Focused Ultrasound Technique in Glioblastoma Multiforme Treatment - Mungur, Rajneesh; Zheng, Jiesheng; Wang, Ben; Chen, Xinhua; Zhan, Renya; Tong, Ying (Frontiers in Oncology, 2022)
Glioblastoma is one of the central nervous system’s most aggressive and lethal cancer with poor overall survival. Systemic treatment of glioblastoma remains the most challenging aspect due to the permeability of the blood-brain barrier (BBB) and blood-tumor barrier (BTB), limiting therapeutics extravasation mainly in the core tumor as well as in its surrounding invading areas. It is now possible to overcome these barriers by using low-intensity focused ultrasound (LIFU) in combination with intravenously administered oscillating microbubbles (MBs). Low-Intensity Focused Ultrasound (LIFU) is a non-invasive technique using converging ultrasound waves to modulate the permeability of BBB/BTB to drug delivery in a specific brain/tumor region. This emerging technique has proven to be both safe and repeatable without causing injury to the brain parenchyma including neurons and other structures. Further, LIFU is also approved by the FDA to treat essential tremors and Parkinson’s disease. It is currently under clinical trial in glioblastoma patients as a drug delivery strategy and liquid biopsy for glioblastoma biomarkers. The use of LIFU+MBs is a step-up in the world of drug delivery, where onco-therapeutics of different molecular sizes and weights can be delivered directly into the brain/tumor parenchyma. Initially, several potent drugs targeting glioblastoma were limited to cross the BBB/BTB; however, using LIFU+MBs, diverse therapeutics showed significantly higher uptake, improved tumor control and overall survival across different species. Here, we highlight the therapeutic approach of LIFU+MBs mediated drug-delivery in the treatment of glioblastoma.